2022
DOI: 10.1111/geb.13526
|View full text |Cite
|
Sign up to set email alerts
|

ECOSTRESS reveals pre‐fire vegetation controls on burn severity for Southern California wildfires of 2020

Abstract: Aim: Topography, climate and plant water stress influence the spatial patterns of burn severity (damage to soils and vegetation associated with wildfires); however, the relative importance of these predictors remains contested. We hypothesized that highresolution pre-fire vegetation water stress, measured using evapotranspiration (ET), evaporative stress index (ESI) and water use efficiency (WUE), are strong predictors of burn severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 53 publications
2
11
0
Order By: Relevance
“…In the Australian Black Summer, Brazilian Pantanal and western US fires, the large burn areas were found to be a function of extremely dry conditions (Collins et al, 2022;Coop et al, 2022;Ferreira Barbosa et al, 2022;Pascolini-Campbell et al, 2022;Safford et al, 2022).…”
Section: Changing Fire Regimesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the Australian Black Summer, Brazilian Pantanal and western US fires, the large burn areas were found to be a function of extremely dry conditions (Collins et al, 2022;Coop et al, 2022;Ferreira Barbosa et al, 2022;Pascolini-Campbell et al, 2022;Safford et al, 2022).…”
Section: Changing Fire Regimesmentioning
confidence: 99%
“…In the Australian Black Summer, Brazilian Pantanal and western US fires, the large burn areas were found to be a function of extremely dry conditions (Collins et al, 2022; Coop et al, 2022; Ferreira Barbosa et al, 2022; Pascolini‐Campbell et al, 2022; Safford et al, 2022). Several studies also examined the drivers of fire severity, finding that fire weather and atmospheric aridity (vapour pressure deficit), and drought stress, were all important drivers of fire severity in south‐eastern Australia and the western United States (Collins et al, 2022; Pascolini‐Campbell et al, 2022; Safford et al, 2022). Pascolini‐Campbell et al (2022) identified the importance of terrain in driving fire severity in Southern California, with higher fire severity observed at high elevations and on steep slopes.…”
Section: What Is Driving Extreme Fire Seasons?mentioning
confidence: 99%
See 1 more Smart Citation
“…The recently launched Ecosystem Spaceborne Thermal Radiometer Experiment on Space Station (ECOSTRESS) mission provides daily estimation of water use and demand (i.e., evapotranspiration and evaporative stress index) based on the frequent image acquisition (i.e., multiple times of day with a return frequency of 1–5 days) (Fisher et al., 2020). Despite a short term‐deployment on the space station, ECOSTRESS can help us understand pre‐ and post‐disturbance diurnal ecosystem processes related to vegetation water stress (Pascolini‐Campbell et al., 2022) and productivity (Poulos et al., 2021).…”
Section: Sensors and Platforms For Observing Cz Disturbancementioning
confidence: 99%
“…However, the recent launch of the ECOSTRESS (Ecosystem Spaceborne Thermal Radiometer Experiment on Space Station) mission provides the opportunity to evaluate how pre-fire landscape hydrology influences fire behavior due to the frequent acquisition of landscape water balance data at an ecologically-relevant pixel size of 70 meters (Fisher, 2018). Yet, to my knowledge, only one study has examined how pre-fire vegetation hydrology influences contemporary landscape fires (Pascolini-Campbell et al, 2022). In that study of six fires using ECOSTRESS to investigate its potential as a fire behavior driver, they demonstrated the importance of antecedent plant water stress as a significant driver of high-severity fire.…”
Section: Vegetation Moisture Content and Landscape Water Balancementioning
confidence: 99%